9th AIAA/ASME Joint Thermophysics and Heat Transfer Conference 2006
DOI: 10.2514/6.2006-2946
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Assessment of Data in Catalytic and Transitional Flows for Martian Entry

Abstract: The conditions for a typical run from the MSL phase two study of transition that was performed in the LENS facility have been analyzed to understand the sensitivity to the freestream conditions of the facility. A simplified analysis technique has been used based on energy accounting to freeze specified portions of the chemical or vibrational energy during the expansion process in the nozzle. The effect of freezing this energy results in increased shock standoff distance that better matches the measured shock s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 24 publications
1
39
0
Order By: Relevance
“…For Run 4, the measured shock is significantly farther away than the prediction. In previous work analyzing CO 2 test cases in the reflected shock tunnel facility, this same behavior was observed 30 . In that case as well, the shock stand-off was measured to be larger than predicted by a much more significant margin and the predicted heat transfer decreased significantly with increased shock stand-off distance.…”
Section: Laminar Forebody Cases In Reacting Airmentioning
confidence: 49%
See 1 more Smart Citation
“…For Run 4, the measured shock is significantly farther away than the prediction. In previous work analyzing CO 2 test cases in the reflected shock tunnel facility, this same behavior was observed 30 . In that case as well, the shock stand-off was measured to be larger than predicted by a much more significant margin and the predicted heat transfer decreased significantly with increased shock stand-off distance.…”
Section: Laminar Forebody Cases In Reacting Airmentioning
confidence: 49%
“…At low to medium enthalpy levels with moderate levels of chemical and vibrational non-equilibrium the method has been found to predict a freestream state that correlates accurately with measurements made in the test section. However, at high enthalpies where there is significant chemical and thermal activity, questions remain about the capability of the physical model to describe the very rapid expansion from reservoir to the test section 29,30 .…”
Section: B Candler Nozzle Codementioning
confidence: 99%
“…A follow-up numerical study found that shock shape and stand-off distance matched experimental observation when 42% of the total energy was artificially frozen in vibration. 11 As discussed by the authors, such a result is clearly aphysical and especially so when one considers that the original calculation had 3.6% of the total energy frozen in vibration. Additionally, frozen vibrational energy was seen to have a greater impact upon the shock stand-off distance than frozen chemical energy.…”
Section: A Cubrc Resultsmentioning
confidence: 99%
“…In contrast, several observations have been previously made in the LENS-I reflected shock tunnel in high-enthalpy reacting air and carbon dioxide test gases where macroscopic discrepancies were clearly visible using this comparison technique. [33,34] The comparison of the measured and predicted surface pressure for all six runs is shown in Fig. 12.…”
Section: Experimental Data Comparisons To Cfdmentioning
confidence: 99%